2010
DOI: 10.1007/s00038-010-0169-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, social support and self-rated health among lone mothers in South Korea

Abstract: The findings clearly indicate that lone mothers have poorer self-rated health than partnered mothers do, but this detrimental effect cannot be entirely explained by the socioeconomic and social support-mediating factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
5
23
0
Order By: Relevance
“…Respondents were classified as current smokers or nonsmokers, current drinkers or nondrinkers, and having a BMI above 25 or 25 and below. The responses to self-rated health status were collapsed into two categories: excellent/good and fair/ poor/very poor 20) . Any missing variables were deleted according to the criteria explained in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were classified as current smokers or nonsmokers, current drinkers or nondrinkers, and having a BMI above 25 or 25 and below. The responses to self-rated health status were collapsed into two categories: excellent/good and fair/ poor/very poor 20) . Any missing variables were deleted according to the criteria explained in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As the study contains longitudinal data, the second and third regression models, which include general health at follow-up as criterion, were additionally adjusted for general health status at baseline. The mediating role of social relations is determined by the percentage reduction in the OR for SES after inclusion of the indicators of social relations using the formula ([OR Model 1 -OR Model 1?social relations ]/ [OR Model 1 -1]) 9 100 (Skalicka et al 2009;von dem Knesebeck and Geyer 2007;Kim et al 2010). Percentage change is displayed when OR is statistically significant in the first model which is only adjusted for age and gender (p \ 0.05).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A comparative study found that emotional support explains little of the educational differences in selfrated health among women and men in most European countries (von dem Knesebeck and Geyer 2007), and the 1958 British birth cohort study showed a poor impact of social relations on SES differences in self-rated health (Power et al 1998). Another cohort study illustrated contributions of strong social networks to explain inequalities in mortality; (Skalicka et al 2009) and Kim et al (2010) found out that poorer self-rated health among lone South Korean mothers is partly mediated by social support. A cross-sectional study in the United States found little evidence that social support and social integration mediate the association between SES and self-rated health (Gorman and Sivaganesan 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other aspects, such as social and emotional aspects, may also contribute to SRH. For example, single parents tend to lack social and emotional support in addition to having the burden of child rearing 38) . The importance of other aspects was further supported by our results, which showed that, despite lower income levels, female precarious workers living as couples with children or in single-person households did not suffer from poorer health than their permanent counterparts (see Figs.…”
Section: Discussionmentioning
confidence: 99%